Distinguishing the tremor of Parkinson's disease from essential tremor: finger displacement. (1st March 2014) - Lieberman, Abraham; Dhall, Rohit; Dhanani, Sara; Salins, Naomi; Sadreddin, Arshia; Moguel-Cobos, Guillermo; Pan, Di; Santiago, Anthony; Prigatano, George; Krishnamurthi, Narayanan; Troster, Alexander
<x xml:space="preserve">Abstract</x> Although, the tremor of Parkinson's disease (PD) usually, but not always, differs from essential tremor (ET), there is no simple bedside test to distinguish PD from ET. We believe we have made such an observation. We studied 50 consecutive tremor-dominant PD patients (mean age: 63.4 years; mean disease duration: 4.9 years) and 35 consecutive ET patients (mean age: 64.1 years; mean disease duration: 12.5 years). Among PD patients, 31 had a bilateral tremor and among ET patients, 29 patients had a bilateral tremor. Patients sat opposite the examiner and pointed both index fingers at the examiner's index fingers. Then they closed their eyes. Within 15 s, one or rarely both of the patient's index fingers moved, was displaced, either upward or laterally. Finger displacement occurred only with bilateral simultaneous pointing with the patient's eyes closed. All the tremor-dominant PD patients exhibited displacement of an index finger. In 46 patients, it occurred on the side of dominant tremor, in 4, it occurred bilaterally. In 31 of 35 ET patients, no displacement occurred. In 4 of 35 ET patients, it occurred unilaterally on the side of dominant tremor. Odds ratio of distinguishing PD from ET: 89.62 at 95% confidence limits (5.31–1513.4), p = 0. 0018. Sensitivity 100% (0.91–1), specificity 89% (0.72–0.96). Finger displacement can distinguish the tremor of PD from ET. The unilateral movement with eyes closed suggests the tremor of PD unlike ET may impact circuits involving the parietal and supplementary motor cortices.